TAFSIR EMANSIPATORIS AISYAH BINTI ABU BAKAR DALAM AYAT-AYAT TENTANG PEREMPUAN DAN YATIM TAFSIR - Bannan Naelin Najihah; Solehudin Solehudin; Budi Suhartawan (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This research discusses the emancipatory interpretation by Aisha bint Abu Bakar of Qur'anic verses relating to women and orphans. The pre-Islamic period is described as a dark time for women and orphans, where they were part of a marginalised group with low social status and limited access to economic opportunities. The analysis in this study is descriptive-analytical by emphasising Aisyah's interpretation of Qur'anic verses related to women and orphans issues. The approach used is a social and historical approach to understand the context and impact of these interpretations. This research uses descriptive qualitative method with content analysis type. The results showed that Aisha bint Abu Bakar made a major contribution in the interpretation of verses about women and orphans with an emancipatory nature, namely liberation from oppression and dependence. Her interpretation of the verses shows special attention to social issues and the rights of women and orphans, as reflected in QS. Al-Baqarah: 220, 222; An-Nisa: 3, 6, 127, 128; Al-Maidah: 6; and Al-Mujadilah: 1. The overall source of interpretation used by Aisyah is bil ma'tsur.